If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Cos(2x) + -1cos(4x) = o Remove parenthesis around (2x) osC * 2x + -1cos(4x) = o Reorder the terms for easier multiplication: 2osC * x + -1cos(4x) = o Multiply osC * x 2osxC + -1cos(4x) = o Remove parenthesis around (4x) 2osxC + -1cos * 4x = o Reorder the terms for easier multiplication: 2osxC + -1 * 4cos * x = o Multiply -1 * 4 2osxC + -4cos * x = o Multiply cos * x 2osxC + -4cosx = o Reorder the terms: -4cosx + 2osxC = o Solving -4cosx + 2osxC = o Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2osxC' to each side of the equation. -4cosx + 2osxC + -2osxC = o + -2osxC Combine like terms: 2osxC + -2osxC = 0 -4cosx + 0 = o + -2osxC -4cosx = o + -2osxC Divide each side by '-4osx'. c = -0.25s-1x-1 + 0.5C Simplifying c = -0.25s-1x-1 + 0.5C Reorder the terms: c = 0.5C + -0.25s-1x-1
| 44x+2+90=180 | | 48/(-8) | | 4(2y+4)=3(y-6) | | -28=4/5(d) | | 4+11x=-40 | | x+57+x+137=180 | | 6x+11y-10x-8y+9x-7y= | | 4+5(-3x+7)=-9 | | (.1-x)*(.2-x)= | | 48/(-18) | | 50-8x=-6 | | 26+(2y+1)= | | -2=8y+3(y+3) | | (7x-4)(3x+9)=0 | | (x+2)(5x+6)=0 | | -10x+10=-40 | | -5.2(4s+6)-1.7(2s-4)= | | 3(2x+15)=2x+20 | | -5-8x=5 | | 2.8x+1y=747.7 | | 2(x-4)=42 | | -100x-300=300 | | 3z+8=-2z+13 | | c(c-5)=0 | | 27=3/4(y) | | s^3+2s^2-25s=50 | | 6[5-(4x-4)]+7x=0 | | 4w+7=7w-14 | | 3x^2+26x+73=0 | | -5u-8=-2u+1 | | 91=9f+28 | | x+3(x-3)=3x+2+2x |